Socially Responsible Human Resource Management Practices from Employees’ Perspective: A Study in a Malaysian GLC - Jonathan, Victoria; Adruce, Shahren Ahmad Zaidi; Stephen, Donald; Suhaili, Dayang Siti Aisah Abang (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT--Socially responsible human resource management (SRHRM) is a corporate social responsibility directed towards employees in the organization. Increasing awareness on the concept of SRHRM has led to a proliferation of studies documenting the positive effect of SRHRM on employee performance. However, empirical work on SRHRM in emerging economies is still limited. This article aims to fill this knowledge gap by showing the extent to which SRHRM practices are being implemented in the context of Malaysia. Most studies on socially responsible practices of organizations in Malaysia focused on external social responsibilities and the environment. Few organizations focused on socially responsible practices towards their employees. This research utilizes a Likert-type self-administered instrument to capture employees’ perception of SRHRM practices in a government-linked company in Malaysia. SRHRM practices in this study include eight dimensions: staffing, training, employee relations, communication, diversity and equal opportunities, compensation, occupational safety and health, as well as work-family balance. A total of 3,928 participants were included in the study. The instrument was validated using Andrich Rating Scale Model. Overfit and underfit items were subsequently removed. As a result, the unidimensionality of SRHRM subscales is established. Linear Scale Transformation and Rasch Person Plot were adapted to illustrate the extent of Employees’ perception of SRHRM subscales. Results show high subscales’ scores for each of the eight dimensions, indicating a positive perception of SRHRM practices in the organization. The results illustrate that socially responsible policies are being implemented in a Malaysian organization. More importantly, employee perception, and the interpretation of the policies into practices by human resources are vital for organization performance. This study also contributes to further validation of SRHRM measures used in previous literature.